Diagnosis of dysphagia in the practice of a family doctor (clinical cases). - О. A. Rosytska; A. V. Chernilovski (Medičnì Perspektivi)
Dysphagia is an important risk factor for such a serious life-threatening or health-patient complication as aspiration (aspiration pneumonia), dehydration, malnutrition. Prevention of dysphagia in the damage to the nervous system is not possible. However, with the proper evaluation and treatment of disorders that result from dysphagia, it is possible to prevent complications, to take into account this symptom when feeding the patient, carrying out rehabilitation measures and medical treatment. The article presents diagnostic algorithms for the actions of the general practitioner-family doctor in the detection of dysphagia and clinical cases of this syndrome of different etiology.